Community periodontal index of treatment needs index: An indicator of anaerobic periodontal infection - Muthukumar S; Suresh R (Wolters Kluwer Medknow Publications, 2009)
Background : Community periodontal index of treatment needs (CPITN) index is commonly used to measure periodontal disease. It′s uniqueness, apart from assessing the periodontal status, also gives the treatment needs for the underlying condition. Benzoyl-DL-arginine napthylamide (BANA) test is a chair side diagnostic test used to detect the presence of putative periodontal pathogens. We correlated the CPITN scores of patients with BANA test results to assess the validity of CPITN as an indicator of anaerobic periodontal infection. Objectives : The present study was aimed to correlate the CPITN scores with the BANA activity of subgingival plaque. The objective was to assess the validity of CPITN index as indicator of anaerobic periodontal infection. Patients and Methods : A total of 80 sites were selected from 20 patients with generalized chronic periodontitis. After measuring the probing depth with CPITN C probe, the highest score from each sextant was selected according to the CPITN criteria and subgingival plaque samples were collected using a sterile curette and the BANA test was performed. Results : Kendall′s tau-b and Chi- square test were used to assess the correlation between the BANA test results and CPITN scores. Results indicated sensitivity (92.86%), specificity (80%) and agreement (91.25%); indicating the validity of CPITN in assessing anaerobic infection. Conclusion : There was a significant correlation between BANA test results and scores 3 and score 4 of CPITN index (P < 0.001) clearly indicating the presence of anaerobic periodontal infection.